The Icon of Local Culture: Downstream of Tamarind Waste as a Superior Motif Barrier in Indonesia - et. al., Ariesa Pandanwangi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Covid-19 outbreak had caused serious damages for business and tourism in most regions in Indonesia. To overcome the loss, the government of Indonesia came up with Super Priority Tourism Development Program and Special Economic Zones (SEZs) of tourism in Indonesia. The government synergizes with each other to make this program. This program was focused on 2 tourist area; Likupang and Labuan Bajo. The aim of this workshop was to train and prepare young and new entrepreneurs in making Wastra to best support the local tourism. The training utilized tamarind gutta as the main material that acted as cold wax in the making of Batik. Tamarind gutta is made of dried tamarind seeds powder mixed with vegetable fat. It acted as barrier to separate one color to another during the coloring of Batik. It can be used on silk, polyester and cotton. The technique used to apply tamarind gutta is putting it into a piping bag and securing it by tying the bag. Cut the tip of the bag and start placing the tamarind gutta on the cloth. This workshop was expected to expand the production of local crafts. To achieve success in the implementation of this workshop, participants were provided with assistance through the Asset Based Community Development (ABCD) approach which prioritized the utilization of local assets and potentials owned by the local community. There were 30 attendees attending this workshop in total. And through this workshop, attendees had successfully made shawls with their own local motifs such as the sea panorama, palm trees, flowers, etc.